2004
DOI: 10.1086/425049
|View full text |Cite
|
Sign up to set email alerts
|

A DeepK-Band Photometric Survey of Merger Remnants

Abstract: We present K-band photometry for 51 candidate merger remnants to assess the viability of whether spiral-spiral mergers can produce bona fide elliptical galaxies. Using both the de Vaucouleurs r 1/4 and Sérsic r 1/n fitting laws, it is found that the stellar component in a majority of the galaxies in the sample has undergone violent relaxation. However, the sample shows evidence for incomplete phase mixing. The analysis also indicates the presence of ''excess light'' in the surface brightness profiles of nearly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

20
199
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(219 citation statements)
references
References 71 publications
20
199
0
Order By: Relevance
“…Moreover, observations of merging systems and gas-rich merger remnants (e.g., Lake & Dressler 1986;Doyon et al 1994;Shier & Fischer 1998;James et al 1999), as well as poststarburst ( E+A / K+A) galaxies (Goto 2005), have shown that their kinematic and photometric properties are consistent with them eventually evolving into typical $L Ã elliptical galaxies. The correlations obeyed by these mergers and remnants (e.g., Genzel et al 2001;Joseph 2006a, 2006b andreferences above) are similar to, e.g., the observed FP and Kormendy (1977) relations for relaxed ellipticals and consistent with evolution onto these relations as their stellar populations age, as well as the clustering and mass density of ellipticals (Hopkins et al 2007b).…”
Section: Introductionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, observations of merging systems and gas-rich merger remnants (e.g., Lake & Dressler 1986;Doyon et al 1994;Shier & Fischer 1998;James et al 1999), as well as poststarburst ( E+A / K+A) galaxies (Goto 2005), have shown that their kinematic and photometric properties are consistent with them eventually evolving into typical $L Ã elliptical galaxies. The correlations obeyed by these mergers and remnants (e.g., Genzel et al 2001;Joseph 2006a, 2006b andreferences above) are similar to, e.g., the observed FP and Kormendy (1977) relations for relaxed ellipticals and consistent with evolution onto these relations as their stellar populations age, as well as the clustering and mass density of ellipticals (Hopkins et al 2007b).…”
Section: Introductionsupporting
confidence: 76%
“…The infrared emission from ULIRGs is thought to be powered by intense starbursts in their nuclei, originating in central concentrations of gas (e.g., Scoville et al 1986;Sargent et al 1987Sargent et al , 1989, which will leave dense stellar remnants ( Kormendy & Sanders 1992;Hibbard & Yun 1999;Rothberg & Joseph 2004), as predicted theoretically (Mihos & Hernquist 1994c). Moreover, observations of merging systems and gas-rich merger remnants (e.g., Lake & Dressler 1986;Doyon et al 1994;Shier & Fischer 1998;James et al 1999), as well as poststarburst ( E+A / K+A) galaxies (Goto 2005), have shown that their kinematic and photometric properties are consistent with them eventually evolving into typical $L Ã elliptical galaxies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both numerical simulations and observations show that merger remnants that have undergone violent relaxation have surface brightness profiles that follow r 1 = 4 laws (e.g., Toomre & Toomre 1972;Barnes 1988;Hibbard & van Gorkum 1996), even while still showing clear signs of the tidal interactions ( Rothberg & Joseph 2004). Thus, if QSO host galaxies are indeed relatively recent merger remnants, they would most likely have elliptical profiles, but they would also show fine structure indicative of past interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The H I is more extended than the galaxy's main stellar elliptical and dusty-gas disk components. Sensitive CCD optical images of the dust features in NGC 3656 were studied by Balcells (1997) and Rothberg & Joseph (2006), who suggested that the dust is a remnant of a dust-rich merger that involved this galaxy's primary optical elliptical component. Figure 1 shows spectra from five regions that are 4-pixel-wide (or 1.6 kpc-wide at D=45 Mpc) in NGC 3656.…”
Section: The Early-age Major-merger/accretion Elliptical Ngc 3656mentioning
confidence: 99%
“…The galaxies in our sample are all ellipticals in that their luminosity profiles follow the de Vaucoleur, r 1/4 law (e.g., Rothberg & Joseph 2004;Young 2005); however, they represent a spread of merger tracers or ages, from galaxies that have been morphologicaly classified as on-going or early-age major mergers to very-late accretion or quiescent systems (see Table 1). The description of the sample as ellipticals with merger or accretion signatures and star-formation (as we have now shown), or mergers with elliptical components, is consistent with the very last stages of an evolution of mergers to form elliptical galaxies or ellipticals that are in the final stages of relaxation after an accretion or merger event with a gas-rich companion.…”
Section: Introductionmentioning
confidence: 99%